Hydroclimate of the Andes Part I: Main Climatic Features - Espinoza, Jhan Carlo; Garreaud, René; Poveda, Germán; Arias, Paola A.; Molina-Carpio, Jorge; Masiokas, Mariano; Viale, Maximiliano; Scaff, Lucia (Frontiers in Earth Science, 2020)
The Andes is the longest cordillera in the world and extends from northern South America to the southern extreme of the continent (from 11°N to 53°S). The Andes runs through seven countries and is characterized by a wide variety of ecosystems strongly related to the contrasting climate over its eastern and western sides, as well as along its latitudinal extension. This region faces very high potential impacts of climate change, which could affect food and water security for about 90 million people. In addition, climate change represents an important threat on biodiversity, particularly in the tropical Andes, which is the most biodiverse region on Earth. From a scientific and societal view, the Andes exhibits specific challenges because of its unique landscape and the fragile equilibrium between the growing population and its environment. In this manuscript, we provide an updated review of the most relevant scientific literature regarding the hydroclimate of the Andes with an integrated view of the entire Andes range. This review paper is presented in two parts. Part I is dedicated to summarize the scientific knowledge about the main climatic features of the Andes, with emphasis on mean large-scale atmospheric circulation, the Andes-Amazon hydroclimate interconnections and the most distinctive diurnal and annual cycles of precipitation. Part II, which is also included in the research topic “Connecting Mountain Hydroclimate Through the American Cordilleras,” focuses on the hydroclimate variability of the Andes at the sub-continental scale, including the effects of El Niño-Southern Oscillation.